Transduction Mechanisms, Micro-Structuring Techniques, and Applications of Electronic Skin Pressure Sensors: A Review of Recent Advances - Andreia dos Santos; Elvira Fortunato; Rodrigo Martins; Hugo Águas; Rui Igreja (Sensors, 2020)
Electronic skin (e-skin), which is an electronic surrogate of human skin, aims to recreate the multifunctionality of skin by using sensing units to detect multiple stimuli, while keeping key features of skin such as low thickness, stretchability, flexibility, and conformability. One of the most important stimuli to be detected is pressure due to its relevance in a plethora of applications, from health monitoring to functional prosthesis, robotics, and human-machine-interfaces (HMI). The performance of these e-skin pressure sensors is tailored, typically through micro-structuring techniques (such as photolithography, unconventional molds, incorporation of naturally micro-structured materials, laser engraving, amongst others) to achieve high sensitivities (commonly above 1 kPa−1), which is mostly relevant for health monitoring applications, or to extend the linearity of the behavior over a larger pressure range (from few Pa to 100 kPa), an important feature for functional prosthesis. Hence, this review intends to give a generalized view over the most relevant highlights in the development and micro-structuring of e-skin pressure sensors, while contributing to update the field with the most recent research. A special emphasis is devoted to the most employed pressure transduction mechanisms, namely capacitance, piezoelectricity, piezoresistivity, and triboelectricity, as well as to materials and novel techniques more recently explored to innovate the field and bring it a step closer to general adoption by society.